Primary Tuberculous Mastitis (Journal of Surgical Sciences, 2019)
Background: Tuberculous mastitis is a rare entity in patients with mammary diseaseeven in countries where incidence of tuberculosis is high. In Bangladesh, TB is anendemic disease but breast tuberculosis is rarely reported. Its clinical patterns andtreatment strategies are changing day by day.Objective: To analyze the clinical presentations , diagnosis and treatment of tuberculousmastitisMethods: This is a prospective nonrandomized descriptive study to analyze clinicalpresentations, diagnosis and treatment of hundred (100) cases received care for tuberculousmastitis at the Chest Disease Hospital, Rajshahi, from July' 2012 to July' 2016.Diagnosis was made in all patients by cytological examination from suspected lesions,which revealed typical tuberculous lesions. Patient with some atypical presentationsand doubts in the diagnosis needed histopathological examination and Gene x-pert testto exclude idiopathic granulomatous mastitis and concomitant malignancy.Results: Most of the patients were within reproductive age. The disease affecting theright breast in fifty six patients (56%), left breast in forty three patients (43%) andbilateral in one patient (1%). Palpable lump were present in eighteen patients (18%),chronic discharging sinus with or without lump in thirty four (34%) and breast abscesswith or without discharging sinus in eighteen patients (18%),recent abscess drainagescar with lump in thirty patients(30).Medical therapy with anti-tubercular drugs ranging from 9 to 12 months with follow upmonthly was the mainstay of treatment. Surgical intervention reserved for selectedrefractory cases. Extension of anti-tubercular therapy from 9 to 12 or 18 monthsrequired in fifty-eight(58) patients on the basis of slow clinical response. Completeresolution obtained in 92 patients but residual tiny mass in eight patients confirmed byrepeated FNAC to be fibrotic.Conclusion: Treatment is simple but high index of suspicion is the cornerstone fordiagnosis.Journal of Surgical Sciences (2017) Vol. 21 (1) :19-23